Faculty perspectives on blended learning in Jordanian universities: opportunities and challenges - Al Fayyoumi, Khalil; Almousa, Nusaiba Ali; Yassin, Baderaddin (Frontiers in Education, 2025)
Blended learning has become an integral part of higher education. It offers a combination of traditional and digital learning approaches. In Jordanian universities, the effectiveness and adoption of blended learning remain topics of interest, particularly from the perspective of faculty members. This study examines the current status of blended learning in Jordanian universities from the perspective of faculty members. A descriptive Approach was adopted, and a questionnaire was developed and administered to a random sample of 131 faculty members selected from three universities: the University of Jordan, Al-Balqa Applied University, and Amman Arab University. The findings indicate that faculty members’ satisfaction with strategies for engaging with blended learning models was moderate. Additionally, no statistically significant differences were identified in the participants’ perceptions of blended learning status based on gender or years of experience (α = 0.05). The study recommends providing faculty members with training in blended learning methodologies, essential computer applications, and augmented reality technologies to enhance their skills and engagement with blended learning.